Color Stability of Glazed and Polished Dental Porcelains - Caner YÃƒâ€žÃ‚Â±lmaz, DDS, PhD,1 Turan Korkmaz, DDS, PhD,1 HisÃƒâ€šÃ‚Â¸am DemirkoÃƒâ€šÃ‚Â¨ pruÃƒâ€šÃ (Journal of Prosthodontics, 2008)
The purpose of this study was to compare the visual and colorimetric color stability of two ultra low-fusing and three conventional low-fusing porcelains on both glazed and polished surfaces.